SEMBUNG DELAN (Sphaerantus indicus L.) TERHADAP Pseudomonas solanacearum L. PENYEBAB PENYAKIT LAYU PADA TANAMAN TOMAT - Ida Bagus Gede Darmayasa (Bumi Lestari Journal of Environment)
A research entitled “Inhibitid activity of plant fractination extract of Sembung Delan(Sphaeranthus indicus L.) to the causal agent of bacterial wilt on tomato” was carried out to find outthe active fraction of plant extract that responsible for bactericidal activity againt P. solanacearum L.,Results of this study showed that the crude extract of S. indicus inhibited the growth of P.solanacearum L. on PDA. It was indicated by the formation of inhibition zone around the disc loadedwith plant extract at concentration of 0 ppm, 10,000 ppm, 20,000 ppm, 30,000 ppm, 40,000 ppm, and50,000 ppm. From 17 fractions obtained from fractionation, fraction No. XV (eluted with ethylacetate 100%) contains three compunds with Rf value: 0.03; 0.23; 0.35 and fraction No. XVI (elutedwith ethyl acetate 100%) contains four compunds with Rf value: 0.03; 0.14; 0.17; 0.21, effectivityinhibited the growth of P. solanacearum L